2021
DOI: 10.3390/ijms222413249
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate–Glutathione Oxidant Scavengers, Metabolome Analysis and Adaptation Mechanisms of Ion Exclusion in Sorghum under Salt Stress

Abstract: Salt stress is one of the major significant restrictions that hamper plant development and agriculture ecosystems worldwide. Novel climate-adapted cultivars and stress tolerance-enhancing molecules are increasingly appreciated to mitigate the detrimental impacts of adverse stressful conditions. Sorghum is a valuable source of food and a potential model for exploring and understanding salt stress dynamics in cereals and for gaining a better understanding of their physiological pathways. Herein, we evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 94 publications
2
12
0
Order By: Relevance
“…The production of ROS production (H 2 O 2 and O 2 − ) in plant cells increased under stress. Studies have shown that glutathione can improve the salt tolerance of sorghum by scavenging ROS ( Punia et al, 2021 ). In addition, a study on upland cotton plants under lead (Pb) stress proved the importance of GSH in HMS detoxification ( Khan et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The production of ROS production (H 2 O 2 and O 2 − ) in plant cells increased under stress. Studies have shown that glutathione can improve the salt tolerance of sorghum by scavenging ROS ( Punia et al, 2021 ). In addition, a study on upland cotton plants under lead (Pb) stress proved the importance of GSH in HMS detoxification ( Khan et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…POD has a high affinity for its substrate H 2 O 2 and can clear H 2 O 2 and other hydroxyl free radicals . The enzyme system plays a crucial role in eliminating ROS, with the drastic increase in POD activity, being especially critical for maintaining the balance of active oxygen inside the body and reducing oxidative damage . Herein, after being subjected to alkaline salt stress, the SOD and CAT activities of G.…”
Section: Resultsmentioning
confidence: 99%
“…Through the screening of metabolites, differentially accumulated metabolites (DAMs) with criteria FC>1.50, P-value<0.05 and VIP>1 were considered to determine the significant differences between samples (Punia et al, 2021). In DK19, compared with CK, 534 metabolites were up-regulated and 632 metabolites were downregulated after 7 days of treatment (Figure 4A).…”
Section: Screen Of Differentially Accumulated Metabolitesmentioning
confidence: 99%